1985
DOI: 10.1111/j.1471-4159.1985.tb07203.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Density of [3H]Imipramine Binding in Aged Human Brain

Abstract: Aging was associated with an increase in the density of specific binding sites for [3H]imipramine in postmortem specimens of human hypothalamus, frontal cortex, and parietal cortex. In general, [3H]imipramine binding was not affected by factors considered difficult to control in postmortem studies, i.e., time from death to autopsy and cause of death. The in vitro regulation of [3H]imipramine binding by sodium was impaired with age in hypothalamic homogenates. In vitro regulation of [3H]imipramine binding by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 39 publications
(46 reference statements)
3
18
0
Order By: Relevance
“…It is interesting to note that similar results have been obtained in the cerebral cortex of aged animals (Brunello et al, 1988) and in the frontal cortex of aged volunteers (Severson et al, 1985). This further supports the hypothesis that circulating lymphocytes and platelets are a convenient tissue and a readily accessible model to study human neurotransmitter receptor systems since changes in these peripheral cells may reflect alterations in receptor responsiveness in a less accessible target tissue as the brain.…”
Section: Discussionsupporting
confidence: 65%
“…It is interesting to note that similar results have been obtained in the cerebral cortex of aged animals (Brunello et al, 1988) and in the frontal cortex of aged volunteers (Severson et al, 1985). This further supports the hypothesis that circulating lymphocytes and platelets are a convenient tissue and a readily accessible model to study human neurotransmitter receptor systems since changes in these peripheral cells may reflect alterations in receptor responsiveness in a less accessible target tissue as the brain.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast to the decrease in 5-HT-sensitive [3H]imipramine binding in the cingulate gyrus, the [3H]paroxetine binding was stable with age. In a study on desipramine-sensitive [3H]imipramine binding in human hypothalamus, an age-related increase was noted [2], However, this increase was likely to be explained by an increase in non specific binding [4], The present study, on the contrary, suggests and age-stability of the hy pothalamic 5-HT uptake sites.…”
Section: Discussionmentioning
confidence: 50%
“…In previous studies on the effect of aging of the 5-hydroxytryptamine (5-HT, serotonin) system, [3H]imipramine binding to the 5-HT uptake site has been used as an indirect marker for 5-HT terminals [1,2]. The initial data on desipramine-sensitive [3H]imipra-mine binding revealed age-related increases in binding density in frontal and parietal cor tices and in the hypothalamus [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between 3H-imipramine and 3H-paroxetine binding to human brain has demonstrated that although it is possible to measure the neuronal serotonergic transport complex by the use of 3H-imipramine, (Langer et al, 1987;Severson et al, 1985;Raisman et al, 1979), paroxetine is a more specific inhibitor of serotonin uptake than imipramine, which may indicate that it is a better candidate for labelling the serotonin transport complex (Mellerup et al, 1986;Marcusson et al, 1988;Plenge et al, 1990;Hrdina, 1990a,b;Arranz et al, 1994).…”
Section: Introductionmentioning
confidence: 97%